Konsep Pendidikan Bermutu Wujudkan Sekolah Unggul - Meti Fatimah; Nur Ayu Setyariza; Sri Erna Widayati; Intan Kusuma Wardani; Yekti Handayani (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
Quality schools are one of the important pillars in building a quality education system in a country. This article discusses the concept of quality schools, factors that influence the quality of education, and challenges faced in realizing quality schools in Indonesia. Through a comprehensive approach, this article identifies several key indicators that can be used to measure school quality, including teacher quality, relevant curriculum, adequate facilities and infrastructure, and community involvement. In addition, this article also discusses the role of government policies and efforts to improve teacher professionalism in achieving the goals of quality education.